Inventory of dragonflies (Odonata) at Sarasah Aia Angek, Harau Valley Nature Park, West Sumatra - Yulita, Rahma; Satria, Rijal (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Sarasah Aia Angek is one of the waterfalls in the Harau Valley Natural Tourism Park which is rarely visited by tourists because of its difficult location to reach. Even though Sarasah Aia Angek is rarely visited by tourists, there is still trash scattered there. It will damage the ecosystem and will affect the diversity of species there, one of which is dragonflies. This study aims to be able to monitor dragonfly species in Sarasah Aia Angek. Sampling of dragonflies within a 10 meter radius from the edge of the waterfall pool and in small rivers that are still connected to the waterfall by direct collection using an insect net. Sampling was carried out at 10.00-18.00 WIB. Dragonfly samples obtained will be preserved and identified. The total individuals found in Sarasah Aia Angek were 26 individual dragonflies which were identified into 5 species, 4 genera and 3 families. All dragonfly species found belong to the Zygoptera sub-order.